Celebrating 50 years of the revista interamericana de psicologia/interamerican journal of psychology: a content analysis - Torres Fernandez, Ivelisse (2017)
The Revista Interamericana de Psicologia/Interamerican Journal of Psychology (RIP/IJP) was first published in 1967. During its fifty-year history, the goal of the journal has been to promote collaboration and communication among psychologists on the Americas through the dissemination of theoretical and applied research. The authors reviewed 1,200 articles published in the RIP/IJP between 1967 and 2016 (Volumes 1-50). The articles were coded into seven main content categories, which included type of article, research design, sample characteristics, data collection strategies, data analysis, thematic analysis, and author’s characteristics and affiliations. Results indicated that up to date, 2,688 authors from 30 identified countries have contributed research on a diverse array of psychological topics on primarily three languages: Spanish, English, and Portuguese. Data also suggest these articles are characterized by a broad range of research methodologies, data collection procedures and analysis, and sample characteristics.